Determinants Of The Event Of Drug Resistant Tuberculosis In The City Of Palembang In 2021 - Ranti Yuliana Putri Putri; Rico Januar Sitorus; Muhammad Zulkarnain (Science Midwifery, 2022)
Tuberculosis is still the main infectious disease in the world, Indonesia ranks 2nd with the highest cases of Tuberculosis after India and China. Drug-resistant tuberculosis is still a threat in tuberculosis control and is a public health problem. Purpose: Analyze the relationship between knowledge, patient motivation, previous treatment history, drug side effect status, the role of drug supervisors, stigma, drug swallowing compliance, tuberculosis treatment length, history of nutritional status, distance from home to fasyankes, previous treatment results, and concomitant diseases against the incidence of drug-resistant tuberculosis in palembang city in 2021. Research conducted using quantitative methods with case control study design. This data is primary and secondary data. The population in this study is all tuberculosis patients in palembang as many as 5,989. The sample in this study was 140 respondents selected based on the SRS method. Data analysis is carried out by univariate, bivariate and finally multivariate analysis. Results: There are seven variables associated with the incidence of drug-resistant tuberculosis, namely the history of previous treatment (p-value = <0.0001%), the status of drug side effects (p-value = <0.0001%), drug swallowing compliance (p-value = 0040%), duration of treatment (p-value = <0.0001), distance from home to health care facilities (p-value = <0.0001%), previous treatment results (p-value = <0.0001%) and concomitant diseases (p-value = 0.004%). The results of the multivariate analysis showed that the variable status of bad drug side effects (p-value = <0.0001%), is the most dominant variable affecting the incidence of drug-resistant tuberculosis in the city of Palembang, after being controlled by previous treatment history, drug side effects, duration of treatment, home distance to health facilities, drug swallowing supervisors, concomitant diseases and drug swallowing compliance (PR = 8,085, 95% CI: 2,596-25,183).